Transcriptional Changes on Blight Fruiting Body of Flammulina velutipes Caused by Two New Bacterial Pathogens - Wang, Qing; Guo, Mengpei; Xu, Ruiping; Zhang, Jingcheng; Bian, Yinbing; Xiao, Yang (Frontiers in Microbiology, 2019)
A blight disease of Flammulina velutipes was identified with symptoms of growth cessation of young fruiting bodies, short stipe and brown spots on the pileus. The pathogenic bacteria were identified as Arthrobacter arilaitensis and Pseudomonas yamanorum by Koch's postulate, gram staining, morphological and 16S ribosomal RNA gene sequence analyses. Either of the pathogenic bacteria or both of them can cause the same symptoms. Transcriptome changes in blighted F. velutipes were investigated between diseased and normal samples. Compared to the control group, 1,099 differentially expressed genes (DEGs) were overlapping in the bacteria-infected groups. The DEGs were significantly enriched in pathways such as xenobiotics metabolism by cytochrome P450 and tyrosine metabolism. Based on weighted correlation network analysis (WGCNA), the module most correlated to the pathogenic treated F. velutipes samples and candidate hub genes in the co-regulatory network were identified. Furthermore, a potential diseased mechanism involved in cell wall disruption, phenolic substrate oxidation and stress defence response was proposed based on the up-regulation of differentially expressed genes encoding exo-beta-1,3-glucanase, tyrosinase, cytochrome P450, MFS transporter and Clavaminate synthase-like protein. This study provides insights into the underlying reactions of young fruiting body of F. velutipes suffering from blight disease and facilitates the understanding of the pathogenic procedure of bacteriosis in edible mushrooms.